Pengaruh Pembelajaran Klasifikasi Makhluk Hidup Menggunakan LKPD Berorientasi Etnobotani Pada Siswa SMP Untuk Meningkatkan Kemampuan Berpikir Kritis dan Kreatif Siswa - Mefi Andriani; Nugroho, Ary Susatyo; Hayat, Muhammad Syaipul (PGRI Kota Semarang, 2025)
This study aims to analyze the effect of learning to classify living things using ethnobotany-oriented Student Worksheets (LKPD) on the critical and creative thinking skills of junior high school students. The study used a quasi-experimental method with a pretest-posttest control group design. This approach uses a Research and Development (R&D) approach. This method was chosen to determine the validity and practicality of developing learning media, as well as the effectiveness of using project-based learning media with an ethnobotanical approach to improve critical and creative thinking skills. Meanwhile, the development model used is the ADDIE model. The subjects were 33 seventh-grade students divided into an experimental class and a control class. Data collection was carried out through a validated critical and creative thinking ability test. The results showed that the use of ethnobotany-oriented LKPD significantly improved students' critical and creative thinking skills compared to conventional learning. Learning that integrates local wisdom is able to provide a real context that strengthens students' analysis, synthesis, and creativity in understanding the classification of living things. Thus, ethnobotany LKPD can be recommended as an alternative science learning media in junior high schools.